Strategic Management Practices in Dynamic Business Environments - Anahera Oganda, Putri; Fredrin Terizla, Rizky (APTISI Transactions on Management (ATM), 2024)
This research delves into an exploration of strategic management practices within organizations operating in dynamically changing business environments. The primary objective is to provide insightful perspectives on how businesses adeptly navigate and adapt their strategies to not only endure but thrive amid swift and continuous changes. Employing a robust mixed-methods approach, the study integrates quantitative analysis derived from survey data with qualitative examination through case studies. The quantitative facet involves collecting and analyzing survey data from a diverse array of businesses in dynamic environments. This survey aims to quantify various strategic management practices, offering statistical insights into the prevalence and effectiveness of different strategies. Simultaneously, the qualitative component encompasses in-depth case studies conducted on select organizations. Through interviews, document scrutiny, and direct observation, this phase seeks to unravel nuanced insights into specific strategic practices responding to dynamic business conditions. Key findings from this dual-method approach shed light on the factors contributing to effective strategic management in dynamic contexts. The discussion emphasizes the significance of adaptability, innovation, and proactive planning in strategic management practices. These insights have practical implications, offering valuable guidance for practitioners engaged in strategic decision-making, helping businesses enhance their resilience and competitive positioning in dynamic environments. Furthermore, scholars can use this study as a foundation for further exploration and theoretical development in the field of strategic management. In conclusion, this research significantly contributes to understanding effective strategic management amid dynamic business environments, benefiting both practitioners and scholars.